Central banking in theory and practice - Blinder, Alan S. (Cambridge, Mass. : MIT Press, 1998)
This book deals succinctly, in a nontechnical manner, with a wide variety of issues in monetary policy. The book also includes the author's suggested solution to an age-old problem in monetary theory: what it means for monetary policy to be neutral. It tells central bankers how they might better incorporate academic knowledge and thinking into the conduct of monetary policy.
Includes bibliographical references (p. [83]-87) and index.
nmn 30/05/13; oif 12/02/15
Loans
Keywords: Banks and banking, Central; Monetary policy; Central banking, theory; United States